Upaya Guru dalam Meningkatkan Kemampuan Berbahasa Jawa Siswa Kelas V melalui Pembiasaan Berbahasa - Khubni Maghfirotun; Muhammad Robik (IBTIDA', 2021)
Language ability is the ability of an individual to make words or sounds that are combined into a complete speech or sentence that can be understood by himself and others. Where individuals can understand speech / language conveyed by others and are able to show or pronounce the language of others. The importance of a teacher's efforts to improve the language skills of students or learners in learning, especially Javanese language learning, must really be done in order to create a quality generation and of course can cultivate the language that becomes their identity. The effort of a teacher in this case is to use the habituation method. This study aims to determine what efforts are made by the teacher inimproving the Javanese language skills of grade V students at MI Miftahul Ulum Pelangwot and to find out what are the supporting factors in improving the Javanese language skills of grade V students at MI Miftahul Ulum Pelangwot. This research uses qualitative methods, with data collection techniques used are: observation, interviews and documentation. The author uses data analysis techniques in the form of qualitative descriptive. Based on the analysis of the data obtained, the researcher can conclude that the efforts of Javanese language teachers in improving students 'language skills are indeed very important to do. The efforts of Javanese language subject teachers to improve students' language skills are through habituation activities, a teacher always provides an example that can be applied by students, as an effort to improve the language skills of students. In addition, the habits that are always applied by the teacher are by carrying out activities related to language skills, such as language habituation in every lesson, holding competitions that are related to the language skills of students.